A histochemical reporter system to study extracellular ATP response in plants - Sowders, Joel M.; Tanaka, Kiwamu (Frontiers in Plant Science, 2023)
When cells experience acute mechanical distress, they release ATP from their cellular compartment into the surrounding microenvironment. This extracellular ATP (eATP) can then act as a danger signal—signaling cellular damage. In plants, cells adjacent to damage detect rising eATP concentrations through the cell-surface receptor kinase, P2K1. Following eATP perception, P2K1 initiates a signaling cascade mobilizing plant defense. Recent transcriptome analysis revealed a profile of eATP-induced genes sharing pathogen- and wound-response hallmarks—consistent with a working model for eATP as a defense-mobilizing danger signal. To build on the transcriptional footprint and broaden our understanding of dynamic eATP signaling responses in plants, we aimed to i) generate a visual toolkit for eATP-inducible marker genes using a β-glucuronidase (GUS) reporter system and ii) evaluate the spatiotemporal response of these genes to eATP in plant tissues. Here, we demonstrate that the promoter activities of five genes, ATPR1, ATPR2, TAT3, WRKY46, and CNGC19, were highly sensitive to eATP in the primary root meristem and elongation zones with maximal responses at 2 h after treatment. These results suggest the primary root tip as a hub to study eATP-signaling activity and provide a proof-of-concept toward using these reporters to further dissect eATP and damage signaling in plants.